2010
DOI: 10.1161/strokeaha.110.586883
|View full text |Cite
|
Sign up to set email alerts
|

Lenticulostriate Arterial Lumina Are Normal in Cerebral Autosomal-Dominant Arteriopathy With Subcortical Infarcts and Leukoencephalopathy

Abstract: Background and Purpose-Cerebral autosomal-dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is a hereditary small vessel disease. Although postmortem studies have demonstrated mural thickening in leptomeningeal arteries and lenticulostriate perforating arteries, it is unclear whether this also leads to luminal narrowing. High-field MRI scanners enable in vivo imaging of the lumen of the lenticulostriate arteries. The aim of this study is to examine the luminal diameters of lenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 24 publications
5
29
1
Order By: Relevance
“…A recent study examining hypertensive patients also showed them to have fewer stems and branches of LSAs than in NC [4]. In contrast, one 7 T MRI study found no difference between patients with cerebral autosomal-dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) and NC in the measurements of LSAs [19]. This discrepancy may be explained by differences in analysis methods (a three-dimensional model in our study versus a two-dimensional model in the previous study) and subject populations (patients with sporadic SVaD in our sample versus patients with a genetic form of small vessel disease in the previous study).…”
Section: Discussionmentioning
confidence: 94%
“…A recent study examining hypertensive patients also showed them to have fewer stems and branches of LSAs than in NC [4]. In contrast, one 7 T MRI study found no difference between patients with cerebral autosomal-dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) and NC in the measurements of LSAs [19]. This discrepancy may be explained by differences in analysis methods (a three-dimensional model in our study versus a two-dimensional model in the previous study) and subject populations (patients with sporadic SVaD in our sample versus patients with a genetic form of small vessel disease in the previous study).…”
Section: Discussionmentioning
confidence: 94%
“…The benefits of using ultra-high magnetic field (UHF) MR scanners for time of flight (TOF) angiography have been shown in studies performed at 7T by several groups 1-8 . These benefits relate with higher spatial resolution, better vessel-to-background contrast as well as increased small vessel conspicuity and are mostly the result of longer T 1 relaxation time 9 and of higher SNR 10 inherently observed as the magnetic field increases.…”
Section: Introductionmentioning
confidence: 99%
“…In addition the increase in SNR can be traded for a very high spatial resolution. In a recent study this was confirmed by visualization of significant lengths of the lenticulostriate arteries (22) in patients with CADASIL and control subjects. Figure 1 shows an example of a coronal maximum intensity projection of the lenticulostriate arteries in a healthy control subject and in a patient with CADASIL.…”
Section: Neurodegenerative Diseasesmentioning
confidence: 67%
“…No significant differences were found between patients and controls in any of the measures. In addition no association was found between the luminal diameters and lacunar infarct load in the basal ganglia and basal ganglia hypointensities on separately acquired T 2 -, T 2 * - or T 1 -weighted scans (22). These results suggest that basal ganglia damage in CADASIL is likely not caused by vascular mechanisms.…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%